The Influence of Lo-Fi Music on Learning Motivation in Padang State University Students - Fauzan, Azka; Fadhatul Al Hatta; Lunadila (Causalita, 2025)
This study aims to explore the impact of Lo-Fi music on students' learning motivation. The background of this study is rooted in the high academic pressure that can lead to decreased learning motivation among students. Lo-Fi music is considered to be able to create a supportive learning environment and increase concentration. The method used in this study was an experiment with a one-group pretest-posttest design. A total of 11 students who experienced decreased learning motivation were selected as samples through a purposive sampling technique. The treatment given was in the form of three Lo-Fi music listening sessions. Data were collected using a learning motivation scale developed by Cherniss and Goleman (2001). The results of the analysis using a paired sample t-test showed a significant difference between the pretest and posttest (p = 0.001), indicating that Lo-Fi music has a positive effect on increasing learning motivation. These findings contribute to the application of music as an alternative relaxation method in educational contexts.